A role for myosin VI in actin dynamics at sites of membrane remodeling during Drosophila spermatogenesis. - Rogat, A.D.; Miller, K.G. (Journal of Cell Science, 2002)
Myosin VI has been implicated in membrane dynamics in several organisms. The mechanism of its participation in membrane events is not clear. We have used spermatogenesis in Drosophila to investigate myosin VI's in vivo role. We demonstrate that myosin VI colocalizes with and is required for the accumulation of the actin polymerization regulatory proteins, cortactin and arp2/3 complex, on actin structures that mediate membrane remodeling during spermatogenesis. In addition, we show that dynamin localizes to these actin structures and that when dynamin and myosin VI function are both impaired, major defects in actin structures are observed. We conclude that during spermatogenesis myosin VI and dynamin function in parallel pathways that regulate actin dynamics and that cortactin and arp2/3 complex may be important for these functions. Regions of myosin VI accumulation are proposed as sites where actin assembly is coupled to membrane dynamics.